Impression Techniques Used for Single‐Unit Crowns: Findings from the National Dental Practice‐Based Research Network. Issue 8 (11th January 2017) - McCracken, Michael S.; Louis, David R.; Litaker, Mark S.; Minyé, Helena M.; Oates, Thomas; Gordan, Valeria V.; Marshall, Don G.; Meyerowitz, Cyril; Gilbert, Gregg H.; ,
Abstract: Purpose: To: (1) determine which impression and gingival displacement techniques practitioners use for single‐unit crowns on natural teeth; and (2) test whether certain dentist and practice characteristics are significantly associated with the use of these techniques. Materials and Methods: Dentists participating in the National Dental Practice‐Based Research Network were eligible for this survey study. The study used a questionnaire developed by clinicians, statisticians, laboratory technicians, and survey experts. The questionnaire was pretested via cognitive interviewing with a regionally diverse group of practitioners. The survey included questions regarding gingival displacement and impression techniques. Survey responses were compared by dentist and practice characteristics using ANOVA. Results: The response rate was 1777 of 2132 eligible dentists (83%). Regarding gingival displacement, most clinicians reported using either a single cord (35%) or dual cord (35%) technique. About 16% of respondents preferred an injectable retraction technique. For making impressions, the most frequently used techniques and materials are: poly(vinyl siloxane), 77%; polyether, 12%; optical/digital, 9%. A dental auxiliary or assistant made the final impression 2% of the time. Regarding dual‐arch impression trays, 23% of practitioners report they typically use a metal frame tray, 60% use a plastic frame, and 16% do not use a dual‐arch tray. Clinicians using optical impression techniques were more likely to be private practice owners or associates. Conclusions: This study documents current techniques for gingival displacement and making impressions for crowns. Certain dentist and practice characteristics are significantly associated with these techniques.